2008
DOI: 10.1083/jcb.200801169
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Dicer expression elicits DNA damage and up-regulation of MICA and MICB

Abstract: RNA interference (RNAi) acts constitutively to silence the innate immune response, and innate immunity genes are misregulated in Dicer-deficient Caenorhabditis elegans. Here, we show that inhibition of Dicer expression by RNAi in human cells up-regulates major histocompatibility complex class I–related molecules A and B (MICA and MICB). MICA and MICB are innate immune system ligands for the NKG2D receptor expressed by natural killer cells and activated CD8(+)T cells. We reveal that knockdown of Dicer elicits D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 29 publications
(38 reference statements)
1
65
0
Order By: Relevance
“…To test the effect of DICER1 on miRNA expression in HNSCC cells after CIS exposure, we used scrambled siRNA (5 0 -AATTCTCCGAACGTGTCACGT-3 0 ) and DICER1 siRNA (5 0 -AAGGCTTACCTTCTCCAGGCT-3 0 ) obtained from Dharmacon (Lafayette, CO, USA), as previously described. 40 To maximally inhibit DICER1 expression and keep the cells at optimal density, DNp63a cells were transfected with two rounds of DICER1 siRNA or scrambled siRNA (each at 100 nM). Cells were split 48 h after the first round of DICER1 siRNAs transfection and were transfected again with the same siRNAs for another 24 h along with exposure to Con or 10 mg/ml CIS.…”
Section: Discussionmentioning
confidence: 99%
“…To test the effect of DICER1 on miRNA expression in HNSCC cells after CIS exposure, we used scrambled siRNA (5 0 -AATTCTCCGAACGTGTCACGT-3 0 ) and DICER1 siRNA (5 0 -AAGGCTTACCTTCTCCAGGCT-3 0 ) obtained from Dharmacon (Lafayette, CO, USA), as previously described. 40 To maximally inhibit DICER1 expression and keep the cells at optimal density, DNp63a cells were transfected with two rounds of DICER1 siRNA or scrambled siRNA (each at 100 nM). Cells were split 48 h after the first round of DICER1 siRNAs transfection and were transfected again with the same siRNAs for another 24 h along with exposure to Con or 10 mg/ml CIS.…”
Section: Discussionmentioning
confidence: 99%
“…S6), Dicer (ex 5Ϫ/Ϫ) cells exhibited greater sensitivity to NK cell-mediated lysis. However, a recent study indicated that inhibition of Dicer leads to up-regulation of ligands for the NKG2D receptor, MICA, and MICB via DNA damage (36). Hence, a variety of immunological mechanisms may operate in increased susceptibility of Dicer (ex5 Ϫ/Ϫ) cells against immune surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining assays for the phosphorylated form of histone H2AX ( -H2AX), a widely used marker for double-strand DNA breaks (Foster ER. & Downs JA., 2005), and for the replication protein A 70 (RPA70), a protein that becomes phosphorylated and forms intranuclear foci upon exposure of cells to DNA damage (Zou Y. et al, 2006), revealed that a much higher percentage of Dicer knockdown cells display intense -H2AX foci and RPA foci compared to control cells (Tang KF. et al, 2008b).…”
Section: Decreased Dicer Expression Elicits Dna Damagementioning
confidence: 99%
“…Decreased Dicer expression elicits DNA damage (Mudhasani R. et al, 2008;Peng JC. & Karpen GH., 2009;Tang KF. et al, 2008b).…”
Section: Dicer Dna Damage and Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation